Dust mass accumulation rates calculated for the Surduk loess profile, Serbia - Filyó, Dávid; Sipos, György; Marković, Slobodan B.; Marković, Rastko S.; Perić, Zoran ; 0000-0003-0116-8895; Magyar, Gergő (NATURAL RESOURCES AND ENVIRONMENTAL RISKS: Towards a Sustainable Future, Novi Sad, Serbia, 2023-10-13 - 2023-10-15, 2023)
Normally, the measurement limit for luminescence analysis of quartz is 50-70 ka with the most widely used single aliquot regeneration (SAR) protocol, consequently, the dating of MIS 3 and MIS 4 samples or older is problematic using quartz. However, recent studies propose that the sensitivity-corrected multiple aliquot regenerative dose (SMAR) measurement technique has the potential to extend the dating limit as far back as 130 ka, making quartz luminescence applicable even for MIS 5 sediments. In our study the dust mass accumulation rate (MAR) of the L1 loess layer in the Surduk loess profile was investigated with the SMAR luminescence measurement technique. In the ~14 metres thick L1 layer samples were collected at every 20 cm. This high-resolution sampling can provide a good basis to build up a more reliable age-depth model for MAR calculation. To validate the quartz SMAR ages, the polymineral fraction of samples was subjected to post-nfrared-infrared (pIR50IR290) measurements at ~1 meter intervals. Based on our results we propose, therefore the application of the quartz SMAR protocol when establishing age models for the LGP in the Surduk loess profile. Later, the MAR values combined with the grain size analyses and other proxies can provide valuable information for detailed paleoenvinromental reconstructions in the region.